BAFF is involved in the pathogenesis of IgA nephropathy by activating the TRAF6/NF-κB signaling pathway in glomerular mesangial cells - Cao, Yingjie (Mol Med Rep, 2020)
The aim of the present study was to investigate the involvement of B cell-activating factor (BAFF) in the pathogenesis of IgA nephropathy by activating the tumor necrosis factor receptor-associated factor 6 (TRAF6)/NF-κB signaling pathway in glomerular mesangial cells. For the clinical analysis, blood, urine and kidney tissue samples were collected from 58 patients diagnosed with primary IgA nephropathy by renal biopsy. For the in vitro study, glomerular mesangial cells were divided into five groups: Control (con)-short hairpin RNA (shRNA) (control group); con-shRNA + BAFF (20 ng/ml); con-shRNA + BAFF + BAFF-RFc chimera protein (500 µg/ml); TRAF6-shRNA; and TRAF6-shRNA + BAFF (20 ng/ml). For the in vivo experiments, 60 Sprague-Dawley rats were randomly divided into four groups: Con-small interfering RNA (siRNA) (control group); con-siRNA + IgA (IgA nephropathy group), BAFF-RFc chimera protein (2 µg/ml) + IgA, and TRAF6-siRNA (0.2 µM) + IgA. Reverse transcription-quantitative PCR was performed to evaluate the mRNA expression levels of TRAF6, connective tissue growth factor (CTGF), fibronectin (FN) and NF-κBP65. Western blot analysis was used to detect the protein expression levels of TRAF6, FN, CTGF and phosphorylated-NF-κBP65 in glomerular mesangial cells and kidney tissues. The results revealed that plasma BAFF levels were positively correlated with the severity of pathological damage in patients with IgA nephropathy. In vitro, BAFF induced the mRNA and protein expression of TRAF6, CTGF, FN and NF-κBP65 in glomerular mesangial cells. After the BAFF-RFc chimera protein was added to inhibit the binding of BAFF and BAFF-receptor (-R), this effect was reduced. In vivo, inhibition of the effects of BAFF via injection with the BAFF-R Fc chimera protein reduced kidney damage in rats suffering from IgA nephropathy. The effect on the expression of signaling pathway-associated proteins was also alleviated. In conclusion, BAFF enhanced the expression of fibroblast factors in the kidneys by activating the TRAF6/NF-κB signaling pathway.